Rekonstruksi Pemikiran Tasawuf Kontemporer Ibnu Arabi dan Relevansinya dengan Pendidikan - Nasrudin, Juhana (Addabani: Interdisciplinary Journal of Islamic Education, 2026)
This research is set against the backdrop of the complexity of modern challenges, including pluralism, social fragmentation, environmental degradation, and the crisis of spiritual meaning, which demand a holistic framework. Ibn Arabi's Sufi thought, particularly the concept of Wahdat al-Wujud, is considered to have great potential to offer transformative solutions. The purpose of this research is to reconstruct Ibn Arabi's contemporary Sufi thought, analyze its relevance to addressing these challenges, and examine its implications for education. The methodology is a qualitative approach that includes in-depth textual analysis of Ibn Arabi's main works (Futuhat al-Makkiyah, Fusus al-Hikam), literature reviews, interviews with contemporary Sufi experts, contextual analysis of modern challenges, and case studies of the application of Sufi thought. The results show that the concept of Wahdat al-Wujud provides a philosophical, ethical, and spiritual foundation for appreciating diversity (pluralism), overcoming spiritual alienation and identity crises, and fostering ecological awareness for environmental sustainability. The concept of the Perfect Man offers an ideal model of a human being capable of balancing spiritual and material dimensions and internalizing universal values. Mystical experiences are also considered relevant in providing a deeper meaning to life. Overall, Ibn Arabi's thought offers an inclusive, transformative, and sustainable spiritual framework that can be integrated into modern spiritual discourse, including in the educational realm. The main recommendation of this research is to integrate Ibn Arabi's Sufi principles into educational curricula to develop individuals with holistic, tolerant, environmentally conscious characters and spiritual depth to face the complexities of the times.